Bioenergetics of immune cells to assess rheumatic disease activity and efficacy of glucocorticoid treatment. Issue 2 (1st February 2003) - Kuhnke, A; Burmester, G-R; Krauss, S; Buttgereit, F
Abstract : Objective: To investigate whether activity and glucocorticoid treatment of rheumatic diseases are reflected by selected parameters of cellular energy metabolism of peripheral blood mononuclear cells (PBMC). Methods: PBMC were obtained from 30 healthy volunteers, 28 patients (16 inactive; 12 active) with rheumatoid arthritis, systemic lupus erythematosus, vasculitis, or other autoimmune diseases, and five patients with infectious diseases. Patients with active rheumatic diseases were examined before and 4–5 days after starting, restarting, or increasing the dose of glucocorticoids. Cellular oxygen consumption (as a measure of ATP production), bioenergetic ability to be stimulated, and major ATP consuming processes were measured amperometrically with a Clark electrode. Results: A normal value for oxygen consumption of 3.84 (SEM 0.1) (all data in nmol O2 /min/10 7 cells) independent of sex was found. In patients with inactive disease the respiration rate was slightly higher, but was significantly increased in active patients to 4.82 (SEM 0.33) (p<0.001). PBMC from active patients showed a significantly lower bioenergetic response to a mitogenic stimulus than controls (p<0.05). In stimulated cells from active patients there was a significant reduction in cation transport and protein synthesis. All parameters above were almost normalised within 4–5 days upon optimised treatment with glucocorticoids. For comparison, PBMC from patients with active infectious diseases also showed an increased respiration rate; their response to mitogenic stimulation was even higher. Conclusions: This study shows for the first time that parameters describing the cellular function of PBMC in bioenergetic terms are suitable for ( a ) describing semiquantitatively the activity of a rheumatic disease and ( b ) assessing the therapeutic effect on the disease.